Study of protein mediators “self-formation” processes in rabbit liver arginase as example - Iskandaryan, M. K.; Barseghyan, E. Kh. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
The aim of the work was to study changes in the structure of oligomer during reverse inactivation on the example of a hepatic arginase of a rabbit to understand the unique aspects of type I mammalian hepatic arginase. It was shown that by presence of Ni2+ cation the "self-formed" oligomer is 1.3-1.8 times more active than the reactivated oligomer by presence of Mn 2+ cation. It was also shown that the enzyme’s physiological stimulant Mn2+ almost 20% inhibits the atalytic activity of Ni 2+ oligomer. Աշխատանքի նպատակն է եղել ճագարի լյարդի արգինազ I օրինակով ուսումնասիրել դարձելի ապաակտիվացման գործընթացում օլիգոմերային կառուցվածքի կրած փոփոխությունները, պարզաբանելու համար կաթնասունների լյարդի I տիպի արգինազի յուրահատուկ կողմերը: Պարզվել է, որ Ni2+ կատիոնի առկայությամբ «ինքնահավաքված» օլիգոմերը 1,3-1,8 անգամ ակտիվ է ի համեմատ Mn2+ կատիոնի առկայությամբ ռեակտիվացված օլիգոմերի։ Ցույց է տրվել, որ ֆերմենտի ֆիզիոլոգիական խթանիչ Mn2+ մոտ 20 %-ով արգելակում է §ինքնահավաքված¦ Ni2+ օլիգոմերի կատալիտիկ ակտիվությունը։
Keywords: Կենսաբանություն; Բժշկագիտություն; Կենսատեխնոլոգիա; Բուսաբանություն; Կենդանաբանություն; Ֆիզիոլոգիա; Մանրէաբանություն; Կենսաքիմիա; Կենսաֆիզիկա; Գենետիկա